2005
DOI: 10.2134/agronj2005.0010
|View full text |Cite
|
Sign up to set email alerts
|

Planting Date Effects on Winter Triticale Dry Matter and Nitrogen Accumulation

Abstract: also capture excess plant available N left after primary crops and decrease the potential of NO 3 leaching into Addition of triticale (ϫTriticosecale Wittmack) into more diversiground water. In studies done with rye (Secale cereale fied cropping systems could provide valuable economic and environmental benefits to producers in the U.S. Corn and Soybean Belt. To L.) cover crops, reductions in the mass of leached N maximize triticale value, research was conducted to identify planting ranged from 59 to 77% compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
32
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 18 publications
7
32
0
2
Order By: Relevance
“…Fall, spring, and total HM declined sharply with successive dates of seeding (Figs. 1 through 4), as has also been reported by Schwarte et al (15). Forage production responses to seeding date had a linear component ( P < 0.001) for fall, spring, and total growth in both years, and a quadratic component ( P ≤ 0.001) only for fall and spring growth from plots seeded in 2002.…”
Section: Forage Production and Seeding Date Responsessupporting
confidence: 85%
“…Fall, spring, and total HM declined sharply with successive dates of seeding (Figs. 1 through 4), as has also been reported by Schwarte et al (15). Forage production responses to seeding date had a linear component ( P < 0.001) for fall, spring, and total growth in both years, and a quadratic component ( P ≤ 0.001) only for fall and spring growth from plots seeded in 2002.…”
Section: Forage Production and Seeding Date Responsessupporting
confidence: 85%
“…The respondents commented that positive effects on yield stability could only be assumed if sowing date was adapted to site conditions and wheat cultivar. This ranking could be confirmed by related studies, while site, variety type and cultivar adapted sowing date could help to significantly improve yield stability of cereals [13,64,65]. Additionally, a few respondents mentioned that earlier sowing dates (mid-September) may lead to better root growth in autumn, which can improve the drought tolerance of wheat plants in the following spring.…”
Section: Further Management Practicesmentioning
confidence: 68%
“…Srinivasan et al (1999) reported yield reduction in chickpea due to chilling stress during the reproductive stage in high latitudes and hilly areas of Asia. Several studies have reported that planting date had a significant effect on crop growth and yield (Darby & Lauer, 2002;Hossain et al, 2003;Bhardwaj et al, 2004;Schwarte et al, 2005).…”
Section: Introductionmentioning
confidence: 99%